Servant Leadership on Turnover Intention as a Job Embeddedness Mediating Variable - Saputra, Ahmad Ronal; Andriani, Chichi (Universitas Negeri Padang, 2024)
This study analyzes: (1) the influence of Servant Leadership on Turnover Intention in PDAM City Payakumbuh (2) the influence of Servant Leadership on Job Embeddedness in PDAM City Payakumbuh (3) the influence of Job Embeddedness on Turnover Intention in PDAM City Payakumbuh (4) The Influence of Servant Leadership on Turnover Intention Mediated by Job Embeddednes in PDAM City Payakumbuh. This research is a causal research. The sample of this study were 41 employees of the PDAM City Payakumbuh. The sampling technique was carried out using total sampling. Collecting data using a questionnaire with a Likert scale. The analysis technique used is the SmartPLS 4 software. The results of this study indicate that: (1) Servant leadership has a negatif and significant effect on the Turnover Intention among Payakumbuh City (2) Servant leadership has a significant positive effect on Turnover Intention among Payakumbuh City (3) Job Embeddedness has a negative and significant effect on Turnover Intention among Payakumbuh City PDAM employees (4) Servant leadership has a negative effect on Turnover Intention through Job Embeddedness as a mediating variable in Payakumbuh City PDAM employees